1996
DOI: 10.1093/jmedent/33.1.90
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Dynamics of Ixodes scapularis (Acari: Ixodidae) in a Rural Landscape

Abstract: We studied seasonal, interannual, and both small- and large-scale spatial variation in the abundance of blacklegged ticks, Ixodes scapularis Say, in a semirural landscape in southeastern New York. Using transect drag sampling, we found that ticks were approximately twice as abundant in 1994 as in the preceding 2 yr. In 1994, larval ticks showed a strong peak in activity in late spring, coincident with the nymphal peak that year. All post-egg life stages were more abundant in forested than in shrubby or herbace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
1
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 0 publications
7
77
1
3
Order By: Relevance
“…Sexual bias in tick infestation on rodents might be related to home range (Sonenshine and Stout 1968). With a larger home range than females, males have more opportunities to be infested (Ostfeld et al 1996a). This pattern might be true for T. laurentius as males are documented to cruise on a larger home range than females (Streilen 1982).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual bias in tick infestation on rodents might be related to home range (Sonenshine and Stout 1968). With a larger home range than females, males have more opportunities to be infested (Ostfeld et al 1996a). This pattern might be true for T. laurentius as males are documented to cruise on a larger home range than females (Streilen 1982).…”
Section: Resultsmentioning
confidence: 99%
“…Tick-host associations are driven by complex ecological interactions and tick load dynamic is explained by complementary factors (Brunner and Ostfeld 2008), such as tick life history traits (Daniels and Fish 1990), host sex and age (Zuk and McKean 1996), host behavior (Ostfeld et al 1996a), and climate conditions (Randolph and Storey 1999). Habitat structure (e.g., vegetation heterogeneity and complexity), also influence tick distribution patterns (Schulze and Jordan 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The total density of nymphal Ixodes scapularis (DON) and the density of infected nymphs (DIN) increased substantially from the field interior (21-34 m from the forest edge) to the shallow forest (4 m in) and again from the forest edge (0-10 m) to the forest interior (20-50 m in). Past studies have demonstrated dramatically increased nymphal abundance within forest habitat as compared to herbaceous habitats (e.g., Maupin et al, 1991;Stafford and Magnarelli, 1993;Duffy et al, 1994;Schmidtmann et al, 1994;Ostfeld et al, 1996). Higher abundances in forest than in fields have been interpreted as arising from more favorable abiotic conditions in the former (Maupin et al, 1991;Adler et al, 1992), although higher abundance of rodent hosts for larval ticks in forest (Morris, 1991;Markowski et al, 1998) also likely plays a role (Ostfeld et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Another important issue related to arthropods, soils and habitat structure in urbanized ecosystems is the distribution and abundance of human disease vectors. For example, many studies in urbanized landscapes have reported that local tick abundance-and therefore probability of exposure to lyme disease-is affected by soil microclimate (especially humidity) which is largely determined by interactions among vegetation, detritus and soil (2006) structure (e.g., Ostfeld et al 1996;Guerra et al 2003). Such results can be communicated to the public using habitat structure as a focus because this concept provides a broad framework within which landscape management guidelines that aim to reduce the probability of disease exposure in urbanized ecosystems can be developed.…”
Section: Soil Organismsmentioning
confidence: 99%